Profiling phytochemical compounds, antibacterial activity and mechanisms of action of ginger essential oils‑nanobactericides against erwinia chrysanthemi causing heart rot disease of pineapple - Rafi, Amara; Gunasena, Mahesh Tiran; Zobir, Syazwan Afif Mohd; Kutawa, Abdulaziz Bashir; Wahab, Mohd Aswad Abdul; Zakaria, Mohd Rafein; Ahmad, Khairulmazmi (Springer, 2023)
Ginger essential oil (GEO) nanobactericides were developed to suppress the growth of Erwinia chrysanthemi (syn Dickeya zeae) which causes bacterial heart rot disease in pineapple. This research focus is on the application of GEO-nanobactericide to suppress the growth of the pathogen in vitro and in vivo. Oil in water (O/W) GEO-nanobactericides was prepared by low energy method using ginger essential oils, Tween 80, and water. Physicochemical parameters such as particle size, zeta potential, polydispersity index, antibacterial activity and disease suppression using developed nanobactericide were investigated. Furthermore, the effects of GEO-nanobactericide on the bacterial cell structure were examined using a transmission electron microscope (TEM), and confocal laser scanning microscope (CLSM). The results of the physicochemical characterizations showed that the smallest particle size was 8.4 nm, the zeta potential value was -23.7 mV, and PDI was 0.13. The results of the in vitro study on the evaluation of the efficacy of nanobactericide against E. chrysanthemi were 31.2 and 62.5 µL/mL as the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC), respectively. Based on the modes of action studied using TEM, the GEO-nanobacteriacide disrupted the cytoplasmic membrane and caused the cell membrane to lose its integrity which increased its permeability. The efficacy of 1xMIC, 2xMIC, and 3xMIC of the nanobactericide were examined in the glasshouse study. Findings revealed that treatment T3 (Er + 3xMIC GEO nanobactericide) was the most effective treatment based on the suppression of the disease, with AUDPC value of 614.95 unit2, disease reduction of 50.01, and protection index of 32.47. These findings revealed that developed GEO-nanobactericide had effectively suppressed the growth of E. chrysanthemi and ultimately control the disease in vitro and in vivo.